The Impact of Total Quality Management on Academic Accreditation (An Analytical Study of Some Employees at the University of Nahrain, College of Business Economics) - Jihad, Mohammed Yahya; Bellaaj, Moez (Journal of Ecohumanism, 2024)
The research aimed to know the total quality management and its impact and relationship with academic accreditation in higher education institutions. The research community included the administrative staff and teaching staff at the College of Business Economics - University of Nahrain, and to determine the role of the research variables of total quality management and its dimensions (supporting senior management, continuous improvement, focusing on students, building work teams, training and empowering employees) and the second variable, academic accreditation, in the success and education of educational institutions and achieving scientific and educational goals in terms of job qualifications and their impact on the institution in addition to improving the solidity of these educational institutions. The research shed light on the academic accreditation system, which is considered one of the main and important systems in managing the activities and programs of higher education institutions. To achieve the research objectives, the descriptive analytical approach was used, as studies and research related to the research variables were used in the theoretical aspect. As for the practical aspect, the researcher used the questionnaire to analyze and describe the paragraphs of the questionnaire and the dimensions and variables of the research, and to shed light on the variation and distribution of these elements in the College of Business Economics. The researcher formulated a set of hypotheses that show the relationship of correlation and influence between the variables. The researcher distributed the questionnaire to the research sample of the teaching and administrative staff, whose number was (136). To analyze this questionnaire, the statistical program SPSS and AMOS, one of the SPSS add-ons, were used. This program was used to reach the results and confirm the validity of the hypotheses. In conclusion, a set of conclusions and recommendations were reached, the most important of which is that the teaching staff enjoys efficiency and excellence, which qualifies them to provide a distinguished scientific level. In addition, the college suffers from a shortage in periodic maintenance programs for equipment and means. As for the recommendations, we summarize them by providing material and moral support to faculty members to participate in scientific research and publish in prestigious journals. And encouraging cooperation between departments and various research centers to enhance interdisciplinary research.